2013
DOI: 10.1097/rhu.0b013e3182a6aa0e
|View full text |Cite
|
Sign up to set email alerts
|

Effective Control of Polymyalgia Rheumatica With Tocilizumab

Abstract: Despite their disadvantages, glucocorticoids (GCs) remain a mainstay of therapy for polymyalgia rheumatica (PMR). Second-line antirheumatic and immune-modulatory drugs are not infrequently required because of disease relapses during GC tapering and GC adverse effects. Therapy with methotrexate or with an anti-tumor necrosis factor drug showed modest efficacy in this situation. Tocilizumab (TCZ) is an anti-interleukin 6 receptor antibody that is being recently studied in the treatment of PMR patients who are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Seven similar cases of pure PMR treated by TCZ have previously been reported 7,8,9,10 , while a substantially higher number of patients with GCA have received this biological agent 4,5 . In PMR cases, TCZ was given as a monthly 8 mg/kg infusion with a clinical response observed within 4 to 12 weeks.…”
Section: To the Editormentioning
confidence: 81%
“…Seven similar cases of pure PMR treated by TCZ have previously been reported 7,8,9,10 , while a substantially higher number of patients with GCA have received this biological agent 4,5 . In PMR cases, TCZ was given as a monthly 8 mg/kg infusion with a clinical response observed within 4 to 12 weeks.…”
Section: To the Editormentioning
confidence: 81%
“…A number of studies have reported high serum levels of interleukin (IL)‐6 in patients with PMR, suggesting that IL‐6 may play a crucial role in the pathogenesis of this condition. In addition, many case reports have confirmed that tocilizumab (TCZ), a humanized anti‐IL‐6 receptor antibody, is an effective treatment for PMR or giant cell arteritis with PMR, including patients who were treated with TCZ monotherapy . Recently, the GiACTA study reported the efficacy of TCZ on the induction of remission and GC‐sparing effect on patients with giant cell arteritis, and this study also revealed the possibility of the maintenance of remission induced by TCZ monotherapy after the discontinuation of GCs .…”
Section: Introductionmentioning
confidence: 83%
“…Tocilizumab, used in a few cases thus far,67 68 is currently being studied in a phase 2 trial (clinicaltrials.gov NCT01396317) and results of a study comparing secukinumab, canakinumab and GCs (clinicaltrials.gov NCT01364389) will be available soon.…”
Section: Discussionmentioning
confidence: 99%